E-Training Course Test Apps as a Media for Measuring Students' Academic Abilities - Fatimah, Siti (Journal of Computer Science Application and Engineering (JOSAPEN), 2023)
This study introduces an E-Training application developed to overcome limitations in traditional classroom settings where time constraints and delayed material delivery hinder student development. E-Training, utilizing information technology in education, responds to the evolving landscape of technological advancements and the global need for IT-based teaching concepts. The implementation of this system follows the prototype model, emphasizing iterative development stages, enhancing understanding, reducing risks, and ensuring cost-effective solutions. The research outlines the comprehensive design process involving UML diagrams, including use case, activity, sequence, and class diagrams, to establish a versatile educational platform. It details the system's structure involving three key actors: admin, student, and teacher. Moreover, the study elaborates on the testing phases encompassing black box and white box methodologies. Black box tests validate successful functionalities like logins, data input, and storage across user roles. Meanwhile, white box testing focuses on logic verification, ensuring accurate computations and display of student scores and rankings. Overall, this E-Training application emerges as a solution bridging the limitations of traditional classrooms, offering an adaptable environment for learning and teaching. Its systematic development and successful testing signify a substantial stride towards enhancing educational accessibility and effectiveness in the digital age.